2015
DOI: 10.1039/c4nj02068e
|View full text |Cite
|
Sign up to set email alerts
|

Optical and theoretical studies on Fe3O4–imidazole nanocomposite and clusters

Abstract: The larger surface curvature of nanocrystals reduces steric hindrance between surface binding molecules and provides a larger number of unsaturated dangling bonds on the nanocrystal surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…The bi‐exponential decay fit indicates that NSPI is in two excited states – in excited state I, the styryl ring is perpendicular with the NSPI ring, and in excited state II, the styryl ring is coplanar with the NSPI ring. The X‐ray crystal structure and theoretical calculation show the perpendicular configuration as most stable, and hence, the observed longer lifetime is attributed to the same. The observed bi‐exponential decay indicates that the NSPI–CSZO composite formation is possible with both conformation of NSPI.…”
Section: Resultsmentioning
confidence: 82%
“…The bi‐exponential decay fit indicates that NSPI is in two excited states – in excited state I, the styryl ring is perpendicular with the NSPI ring, and in excited state II, the styryl ring is coplanar with the NSPI ring. The X‐ray crystal structure and theoretical calculation show the perpendicular configuration as most stable, and hence, the observed longer lifetime is attributed to the same. The observed bi‐exponential decay indicates that the NSPI–CSZO composite formation is possible with both conformation of NSPI.…”
Section: Resultsmentioning
confidence: 82%
“…The frequency around 1695 cm −1 corresponds to C=N group of the imidazole and frequency around 1593 cm −1 corresponds to C=C aromatic segments. The peak approximately 3434 cm −1 corresponds to ≥ C−H in the emitter . The frequency around 2958 cm −1 corresponds to CH 2 , CH 3 group of the emitter.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic peaks of all nanocomposites were observed at 2θ = 30°, 35.7°, 43°, 53.4°, 57.0° and 62.6°, which are marked by their respective indices ((220), (311), (400), (422), (511) and (440)) [ 61 ]. This showed that the surface functionalization does not change the crystalline phase of MNPs [ 62 ].…”
Section: Resultsmentioning
confidence: 99%